2022
DOI: 10.1111/ajt.16940
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor superfamily member 25 (TNFRSF25) agonists in islet transplantation: Endogenous in vivo regulatory T cell expansion promotes prolonged allograft survival

Abstract: Regulatory T cells (Tregs) modulate alloimmune responses and may facilitate minimization or withdrawal of immunosuppression posttransplant. Current approaches, however, rely on complex ex vivo Treg expansion protocols. Herein, we explore endogenous in vivo Treg expansion through antibody‐mediated agonistic stimulation of the tumor necrosis factor receptor superfamily member 25 (TNFRSF25) pathway and its potential to prolong graft survival in a mouse model of islet allotransplantation. C57BL/6 male mice were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Of note, recent research has demonstrated that murine CD4 + FoxP3 + T cells can be classified into two subpopulations, with distinct FoxP3 localization based on the expression of CD25; CD4 + CD25 + T cells expressing FoxP3 in the nucleus, whereas CD4 + CD25 − T cells express FoxP3 in the cytoplasm [ 52 , 53 ]. In the present study, we observed both the nuclear and cytoplasmic localization of FoxP3 within long-term functional allografts, consistent with the findings of other modalities to prevent murine islet allograft rejection [ 54 , 55 ]. As such, we will also characterize and quantify CD4 + CD25 + Foxp3 + Treg and CD4 + CD25 − Foxp3 + Treg populations to better understand the role of these populations in murine islet allograft engraftment and rejection.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, recent research has demonstrated that murine CD4 + FoxP3 + T cells can be classified into two subpopulations, with distinct FoxP3 localization based on the expression of CD25; CD4 + CD25 + T cells expressing FoxP3 in the nucleus, whereas CD4 + CD25 − T cells express FoxP3 in the cytoplasm [ 52 , 53 ]. In the present study, we observed both the nuclear and cytoplasmic localization of FoxP3 within long-term functional allografts, consistent with the findings of other modalities to prevent murine islet allograft rejection [ 54 , 55 ]. As such, we will also characterize and quantify CD4 + CD25 + Foxp3 + Treg and CD4 + CD25 − Foxp3 + Treg populations to better understand the role of these populations in murine islet allograft engraftment and rejection.…”
Section: Discussionsupporting
confidence: 91%
“…TNFRSF25 regulates the activity of both CD4 + T cells and CD8 + T cells, it serves as a costimulatory receptor for memory CD8 + T cells and can increase the accumulation and proliferation of antigen-speci c CD8 + T cells, thus TNFRSF25 agonist can be used to elicit anti-tumor CD8 + T cells 36 . A recent study on TNFRSF25 indicated that its antibodies (4C12 or mPTX-35) can enhance the Treg expansion and prolonged the survival of allograft 37 . BIRC5 (Baculoviral IAP repeat containing 5, also known as Survivin) is a member of the apoptosisinhibiting protein family, it is only expressed in actively proliferating cells, especially in tumor and embryonic tissues, and is closely related to the differentiation, proliferation, invasion and metastasis of tumor cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, widely-adopted chemotoxic methods to destroy β cells and induce diabetes in rodents, like STZ challenge 3 , 4 , 23 , are known to cause undesired off-target damage to cells in the liver, nervous system, cardiovascular system, respiratory system, kidneys, and reproductive system 4 . STZ challenge may also confound studies of transplantation tolerance, because of the association of STZ administration with decreased T cell numbers 24 , 25 . In addition to undesirable effects, previous studies directly comparing the STZ and RIP-DTR models demonstrated variable, lower efficiency of β cell ablation with STZ challenge 10 , and spontaneous recovery from STZ-induced diabetes 26 .…”
Section: Discussionmentioning
confidence: 99%